1993
DOI: 10.1111/j.1432-1033.1993.tb18000.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of V2 [8‐lysine] vasopressin and oxytocin receptors from a pig kidney cell line

Abstract: [Arg*]vasopressin and oxytocin are the two main members of the neurohypophysial hormone family found to be present in nearly all mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 41 publications
2
67
1
Order By: Relevance
“…The structure of the OTR has been elucidated by molecular cloning in different mammalian species (Kimura et al 1992, Gorbulev et al 1993, Bathgate et al 1995, Riley et al 1995, Rozen et al 1995. The deduced amino acid sequences indicated that this receptor belongs to the G protein-coupled receptor family.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the OTR has been elucidated by molecular cloning in different mammalian species (Kimura et al 1992, Gorbulev et al 1993, Bathgate et al 1995, Riley et al 1995, Rozen et al 1995. The deduced amino acid sequences indicated that this receptor belongs to the G protein-coupled receptor family.…”
Section: Introductionmentioning
confidence: 99%
“…GPCRs mediate the actions of numerous neurotransmitters and hormones (Probst et al 1992). The V2 receptor mediates the antidiuretic effects of VP and couples positively to adenylate cyclase (Lolait et al 1992, Gorbulev et al 1993. The OT receptor (Kimura et al 1992, Gorbulev et al 1993 mediates various central and peripheral functions in reproduction in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…The V2 receptor mediates the antidiuretic effects of VP and couples positively to adenylate cyclase (Lolait et al 1992, Gorbulev et al 1993. The OT receptor (Kimura et al 1992, Gorbulev et al 1993 mediates various central and peripheral functions in reproduction in mammals. V1a (Thibonnier et al 1994) and V1b (Sugimoto et al 1994) receptors mediate the effects of VP on liver glycogenolysis and the release of adrenocorticotropin, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…So far, three AVP receptors subtypes, V 1a , V 1b , and V 2 have been identified based upon their primary structure (3)(4)(5)(6)(7)(8)(9)(10), their coupling mechanisms, their tissular distributions and their pharmacological properties (for review see 11,12). The V 2 receptor belongs to the seven transmembrane G proteincoupled receptor superfamily and is positively coupled to a Gs/ adenylyl cyclase system.…”
Section: Introductionmentioning
confidence: 99%